2017
DOI: 10.1097/ta.0000000000001258
|View full text |Cite
|
Sign up to set email alerts
|

When are CT angiograms indicated for patients with lower extremity fractures? A review of 275 extremities

Abstract: Diagnostic test, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…It is quick and readily available, with relatively few contraindications or complications. We had no adverse effects or extra morbidity from the additional angiography sequence in our series, and this correlates with other studies [ 16 ]. The vast majority of trauma patients have a CT head to pelvis, and therefore, angiography may be suitable with little extra ionising radiation or risk.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is quick and readily available, with relatively few contraindications or complications. We had no adverse effects or extra morbidity from the additional angiography sequence in our series, and this correlates with other studies [ 16 ]. The vast majority of trauma patients have a CT head to pelvis, and therefore, angiography may be suitable with little extra ionising radiation or risk.…”
Section: Discussionsupporting
confidence: 90%
“…However, the presence of open fracture, distal or shaft tibial fractures increases the risk of having vascular injury on CTA. They also concluded that all their patients who had diminished or absent pulses required vascular treatment and therefore emphasise how important clinical examination is [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was rarely described in existing fracture models. CTA is a unique radiographic method that demonstrates the arterial vasculature structures through 3D volumetric reconstruction which could rapidly detect vascular injuries [24]. In our study, CTA results showed moderate and partial vascular injuries in group 3 (2/36) and obvious vascular injuries in group 4 (36/36) ( Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Many of these patients are taken directly to theatre and therefore do not undergo radiological investigation. In a recently published study by Monazzam et al [24] on CT angiograms of fractured lower extremities, they found no evidence to support the routine use of CT angiograms to evaluate lower-extremity fractures unless at least one hard or soft vascular sign was present. The data of the current study do not describe the indication for scans outside of blunt trauma, penetrating trauma and non-trauma; therefore, the lower yield rates may be due to scans being done without specific indications, as mentioned above.…”
Section: Researchmentioning
confidence: 99%